The Effect of Division of Labor and Employee Authority on Employee Performance CV. Karya Mega Mandiri Binjai - Ritonga, Jakfar Syahbuddin (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2022)
This study aims to determine whether the division of labor and employee authority has a significant positive effect, partially or simultaneously, on employee performance at CV. Karya Mega Mandiri Binjai. The research was conducted with a questionnaire distributed to 65 samples who were employees of CV. Karya Mega Mandiri Binjai. This type of research is associative research, namely research that aims to determine whether there is an influence of the independent variable on the dependent variable. Data analysis techniques were used in this study using multiple linear regression analysis techniques. The results obtained from this study indicate that the division of labor and employee authority have a significant positive effect partially or simultaneously on employee performance at CV. Karya Mega Mandiri Binjai.